Reading English-language haiku: An eye-movement study of the 'cut effect' - Thomas Geyer; Franziska Günther; Hermann J Müller; Jim Kacian; Heinrich René Liesefeld; Stella Pierides (Bern Open Publishing, 2020)
The current study, set within the larger enterprise of Neuro-Cognitive Poetics, was designed to examine how readers deal with the 'cut' - a more or less sharp semantic-conceptual break - in normative, three-line English-language haiku poems (ELH). Readers were presented with three-line haiku that consisted of two (seemingly) disparate parts, a (two-line) 'phrase' image and a one-line 'fragment' image, in order to determine how they process the conceptual gap between these images when constructing the poem's meaning - as reflected in their patterns of reading eye movements. In addition to replicating the basic 'cut effect', i.e., the extended fixation dwell time on the fragment line relative to the other lines, the present study examined (a) how this effect is influenced by whether the cut is purely implicit or explicitly marked by punctuation, and (b) whether the effect pattern could be delineated against a control condition of 'uncut', one-image haiku. For 'cut' vs. 'uncut' haiku, the results revealed the distribution of fixations across the poems to be modulated by the position of the cut (after line 1 vs. after line 2), the presence vs. absence of a cut marker, and the semantic-conceptual distance between the two images (context-action vs. juxtaposition haiku). These formal-structural and conceptual-semantic properties were associated with systematic changes in how individual poem lines were scanned at first reading and then (selectively) re-sampled in second- and third-pass reading to construct and check global meaning. No such effects were found for one-image (control) haiku. We attribute this pattern to the operation of different meaning resolution processes during the comprehension of two-image haiku, which are invoked by both form- and meaning-related features of the poems.